2022
DOI: 10.1002/adfm.202208761
|View full text |Cite
|
Sign up to set email alerts
|

Percolating Superconductivity in Air‐Stable Organic‐Ion Intercalated MoS2

Abstract: When doped into a certain range of charge carrier concentrations, MoS 2 departs from its pristine semiconducting character to become a strongly correlated material characterized by exotic phenomena such as charge density waves or superconductivity. However, the required doping levels are typically achieved using ionic-liquid gating or air-sensitive alkali-ion intercalation, which are not compatible with standard device fabrication processes. Here, the emergence of superconductivity and a charge density wave ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 66 publications
1
14
1
Order By: Relevance
“…However, the superconductivity in intercalated flakes remains largely unexplored. A first step in this direction was taken by Pereira et al [39] In this work, the authors studied the superconductivity in organic-ion intercalated MoS 2 . While it is well established that MoS 2 can be made superconductor via ionic-liquid gating [47,63] and through the intercalation of alkali metal ions, [28,64] the intercalation of organic cations in MoS 2 had not been previously [39] Copyright 2022, Wiley-VCH.…”
Section: Engineering Superconductivity In Layered Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the superconductivity in intercalated flakes remains largely unexplored. A first step in this direction was taken by Pereira et al [39] In this work, the authors studied the superconductivity in organic-ion intercalated MoS 2 . While it is well established that MoS 2 can be made superconductor via ionic-liquid gating [47,63] and through the intercalation of alkali metal ions, [28,64] the intercalation of organic cations in MoS 2 had not been previously [39] Copyright 2022, Wiley-VCH.…”
Section: Engineering Superconductivity In Layered Materialsmentioning
confidence: 99%
“…Figure a shows that MoS 2 bulk crystals intercalated with tetraethylammonium (TEA) cations display a superconductive transition. [ 39 ] Additionally, the electronic properties of a flake exfoliated from a TEA‐intercalated bulk crystal were also investigated. In this case, while a resistance drop is measured at low temperature, the zero‐resistance state was not reached (Figure 3b).…”
Section: Engineering Superconductivity In Layered Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is highly desired to engineer the interlayer spacing of 2H-MoS 2 to solve its restacking and optimize the pore structure, enhancing the charge-transport properties and charge-storage capability. Recently, it has been shown that the interlayer spacing of MoS 2 can be extended by the insertion of multiple guest molecules or ions, such as water molecules, 24,32 N , N -dimethyl fumarate (DMF), 33 cetyltrimethylammonium bromide (CTAB), 34 NH 4 + ions, 35 poly(3-hexylthiophene) (P3HT) blended with phenyl-C61-butyric acid methyl ester (PCBM), 36 cetyltrimethylammonium (CTA + ), tetramethylammonium (TEA + ), 37 quaternary ammonium molecules, 38 TBAOH, 39 polyethyleneimine, polyethylene glycol, 40 poly(3,4-ethylenedioxythiophene) (PEDOT), 41 phenylenediamine (PPD) and N , N -dimethyl- p -phenylenediamine (DMPD). 42 In detail, Yang's team developed a simple, mild and efficient polymer-direct-intercalation strategy where polyethyleneimine/polyethylene glycol can directly intercalate into the 2H-MoS 2 interlayers, forming interlayer-expanded 2H-MoS 2 /carbon heteroaerogels after carbonization, beneficial for fast charge transport and enhanced pseudo-capacitance.…”
Section: Introductionmentioning
confidence: 99%